Water Treatment Sludge Stabilizer Binder by Waste Paper Sludge Ash for Solidification/Stabilisation Technique - Ismail, Nurliyana; Arshad, Mohd Fadzil; Saman, Hamidah Mohd; Kang, Choong Wee (International Journal of Integrated Engineering, 2019)
Waste Paper Sludge Ash (WPSA) used as stabilizer binder to treat water treatment sludge (WTS). This study was conducted to treat WTS by using WPSA in Solidification/Stabilisation (S/S) technique. 10%, 20%, 30%, 40% and 50% of WPSA was utilized to treat 200g of WTS. 100% of Ordinary Portland Cement (OPC) was used as control specimen. For testing, compressive strength and leaching test on WTS treated with WPSA at specified percentage were performed. It was experimentally done on sample cured at 1, 3, 7 and 28 ages for the compressive strength and at 28 ages for leaching test. Results showed that compressive strength decreases with increasing WPSA content. The immobilization of cadmium (Cd), lead (Pb), nickel (Ni), copper (Cu) and chromium (Cr) were monitored. The concentration of metals decreases with respect to percentage of WPSA added. The optimum content of WPSA to treat WTS was 50%.